Growth and Immune Gene Expression by Dietary Supplementation of Mannan Oligosaccharide in Fry of Deccan Mahseer, Tor khudree - Ranadive, A. B.; Meshram, S. J.; Tibile, R. M.; Pai, R. K.; Hundare, S. K. (International Journal of Bio-resource and Stress Management, 2018)
The present study was conducted during 2017 at wet laboratory of College of Fisheries, Shirgaon, Ratnagiri, Maharashtra, India to evaluate the effect of mannan oligosaccharide on growth and immune gene expression in fry of Deccan mahseer, Tor khudree (Sykes, 1839). In the experiment the fry (0.067±0.02 g) were stocked at a rate of 30 fry/50 L in a plastic tub. The fry was fed with 38% protein diet incorporated with different levels of MOS (0.0 g kg-1, 1.5 g kg-1, 3.0 g kg-1 and 4.5 g kg-1). The fry was fed for 60 days at a rate of 4% of body weight twice a day. The water was exchanged once a day that is in morning session to remove the uneaten feed and faecal matter. Among the experimental diets, the diet containing 3.0 g kg-1 MOS showed significantly higher growth as weight gain (402.43±15.17), length gain (70.023±0.75), specific growth rate (2.62±0.05), average daily growth rate (0.282±0.80) and survival percentage (81.99±1.3) as compared to other diets. Feed conversion ratio was better in diet containing 3.0 g kg-1 of MOS but there was no significant difference among the diets. In the immune gene expression study the primer were designed for the RT-PCR. Among which the housekeeping gene β-actin was amplified at 59 °C. The above results indicate that incorporation of MOS at a rate of 3.0 g kg-1 of feed in diets of Deccan mahseer fry could enhance the growth performance and the feed conversion ratio.